Epigenetic signatures of stress adaptation and flowering regulation in response to extended drought and recovery in Zea mays. (12th November 2019) - Forestan, Cristian; Farinati, Silvia; Zambelli, Federico; Pavesi, Giulio; Rossi, Vincenzo; Varotto, Serena
Abstract: During their lifespan, plants respond to a multitude of stressful factors. Dynamic changes in chromatin and concomitant transcriptional variations control stress response and adaptation, with epigenetic memory mechanisms integrating environmental conditions and appropriate developmental programs over the time. Here we analyzed transcriptome and genome‐wide histone modifications of maize plants subjected to a mild and prolonged drought stress just before the flowering transition. Stress was followed by a complete recovery period to evaluate drought memory mechanisms. Three categories of stress‐memory genes were identified: i) "transcriptional memory" genes, with stable transcriptional changes persisting after the recovery; ii) "epigenetic memory candidate" genes in which stress‐induced chromatin changes persist longer than the stimulus, in absence of transcriptional changes; iii) "delayed memory" genes, not immediately affected by the stress, but perceiving and storing stress signal for a delayed response. This last memory mechanism is described for the first time in drought response. In addition, applied drought stress altered floral patterning, possibly by affecting expression and chromatin of flowering regulatory genes. Altogether, we provided a genome‐wide map of the coordination between genes and chromatin marks utilized by plants to adapt to a stressful environment, describing how this serves as a backbone for setting stress memory. Abstract : Dynamic analysis of transcriptomic and chromatin mark changes after prolonged mild drought stress and recovery period reveals different subsets of genes potentially involved in stress memory in maize.